Endostatin Genetically Engineered Placental Mesenchymal Stromal Cells Carrying Doxorubicin-Loaded Mesoporous Silica Nanoparticles for Combined Chemo- and Antiangiogenic Therapy - Paz de la Torre; Juan L. Paris; Miguel Fernández-de la Torre; María Vallet-Regí; Ana I. Flores (MDPI AG, 2021)
Combination therapies constitute a powerful tool for cancer treatment. By combining drugs with different mechanisms of action, the limitations of each individual agent can be overcome, while increasing therapeutic benefit. Here, we propose employing tumor-migrating decidua-derived mesenchymal stromal cells as therapeutic agents combining antiangiogenic therapy and chemotherapy. First, a plasmid encoding the antiangiogenic protein endostatin was transfected into these cells by nucleofection, confirming its expression by ELISA and its biological effect in an ex ovo chick embryo model. Second, doxorubicin-loaded mesoporous silica nanoparticles were introduced into the cells, which would act as vehicles for the drug being released. The effect of the drug was evaluated in a coculture in vitro model with mammary cancer cells. Third, the combination of endostatin transfection and doxorubicin-nanoparticle loading was carried out with the decidua mesenchymal stromal cells. This final cell platform was shown to retain its tumor-migration capacity in vitro, and the combined in vitro therapeutic efficacy was confirmed through a 3D spheroid coculture model using both cancer and endothelial cells. The results presented here show great potential for the development of combination therapies based on genetically-engineered cells that can simultaneously act as cellular vehicles for drug-loaded nanoparticles.